Survey of the effect of viewing an online e-cigarette advertisement on attitudes towards cigarette and e-cigarette use in adults located in the UK and USA: a cross-sectional study. Issue 6 (18th June 2019) - Booth, Paula; Albery, Ian P; Cox, Sharon; Frings, Daniel
Abstract : Objectives: This study explored the potential for e-cigarette advertisements to (1) enhance attitudes towards cigarettes and/or (2) reduce barriers to e-cigarettes uptake. The study tested whether exposure to an online electronic cigarette advertisement changed attitudes towards cigarettes and e-cigarettes in smokers, non-smokers, e-cigarette users and dual users (smokers who also use e-cigarettes). Design: Cross-sectional study Setting: Online survey Participants: Adults (n=964) aged 18 to 65 years old (M=36 years, SD=11.6) from the UK and USA. Participants were grouped into current non-smokers, e-cigarette users, dual users and smokers. Interventions: Participants viewed 1 of 15 randomly assigned online e-cigarette advertisements. Primary measures: Three single seven-point Likert scales measuring health, desirability, social acceptability were completed pre and post advertisement exposure. Results: Post exposure all smoking groups showed a decrease or no change in how socially acceptable or desirable they rated cigarettes. Paradoxically, dual users rated cigarettes as being significantly healthier after viewing the advertisement (p=0.01) while all other smoking group ratings remained the same. There was an increase or no change in how all smoking groups perceived the healthiness and desirability of e-cigarettes Conclusions: We observed no evidence that exposure to an e-cigarette advertisement renormalises or encourages smoking in smokers, non-smokers or e-cigarette users. However, there is some indication that viewing an e-cigarette advertisement may increase duals users' perceptions of the health of smoking.